U.S. Trends in Hospitalization and Generalist Physician Workforce and the Emergence of Hospitalists - Meltzer, David O. (Springer-Verlag, 2010)
BACKGROUND: General internists and other generalist physicians have traditionally cared for their patients during both ambulatory visits and hospitalizations. It has been suggested that the expansion of hospitalists since the mid-1990s has “crowded out” generalists from inpatient care. However, it is also possible that declining hospital utilization relative to the size of the generalist workforce reduced the incentives for generalists to continue providing hospital care. OBJECTIVE: To examine trends in hospital utilization and the generalist workforce before and after the emergence of hospitalists in the U.S. and to investigate factors contributing to these trends. DESIGN: Using data from 1980–2005 on inpatient visits from the National Hospital Discharge Survey, and physician manpower data from the American Medical Association, we identified national trends before and after the emergence of hospitalists in the annual number of inpatient encounters relative to the number of generalists. RESULTS: Inpatient encounters relative to the number of generalists declined steadily before the emergence of hospitalists. Declines in inpatient encounters relative to the number of generalists were driven primarily by reduced hospital length of stay and increased numbers of generalists. CONCLUSIONS: Hospital utilization relative to generalist workforce declined before the emergence of hospitalists, largely due to declining length of stay and rising generalist workforce. This likely weakened generalist incentives to provide hospital care. Models of care that seek to preserve dual-setting generalist care spanning ambulatory and inpatient settings are most likely to be viable if they focus on patients at high risk of hospitalization.